2018
DOI: 10.1002/aet2.10079
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Institutional Standardized Letter of Evaluation Global Assessment Ranking Practices, Interviewing Practices, and Medical Student Outcomes

Abstract: Background: Emergency medicine (EM) program directors rely largely on the standardized letter of evaluation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…They may be faced with the struggle between objectively assessing students and wanting them to match. Program and clerkship directors likely acknowledge the impact that placing a candidate into the lower categories may have on their competitiveness for a residency position . With only 4 weeks to observe a student, it may also be difficult to neatly place them into a quantile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may be faced with the struggle between objectively assessing students and wanting them to match. Program and clerkship directors likely acknowledge the impact that placing a candidate into the lower categories may have on their competitiveness for a residency position . With only 4 weeks to observe a student, it may also be difficult to neatly place them into a quantile.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to maintain objectivity, SLOE authors may inflate scores . Many SLOE authors do not adhere strictly to quantile categories because they are concerned about negatively impacting a student's ability to match . It is unclear whether students receive higher scores on the group SLOEs from home rotations versus away rotations.…”
mentioning
confidence: 99%
“… 1 , 5 , 6 The SLOE gives readers objective data by ranking students in tertiles in seven categories of “Qualifications for EM.” Additionally students are ranked as the top 10%, top third, middle third, or bottom third for a global assessment and estimated position on the rank list. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Li et al evaluated gender biases in SLOEs and found that the narrative portions were, “relatively free of gender bias.” 8 A study from Pelletier-Bui et al surveyed SLOE writers and found that most SLOE writers did not strictly adhere to the SLOE guidelines citing a fear that a weak evaluation could prevent an applicant from obtaining a position as an EM resident. 7 Girzadas et al studied the precursor to the SLOE, the standardized letter of recommendation, and found that female letter writers were twice as likely to give the highest ranking to female applicants giving a basis for some ingroup bias. 9 Although the effect of home institution on a SLOE was not studied until 2019, 10 Program directors have long held slight preference for a SLOE from an away rotation over a SLOE from their home rotation.…”
Section: Introductionmentioning
confidence: 99%
“…SLOE writers report grade inflation to minimize the risk of applicants not matching, with nearly one-quarter of SLOE writers acknowledging that they “sometimes” or “frequently” inflate GA rankings. 6 , 7 Despite this, the actual impact of a lower-third GA ranking in the SLOE on ultimate match outcome is unknown. Our study is the first, to our knowledge, to directly evaluate the impact of a lower-third GA ranking upon successful match rates in EM using actual NRMP outcomes data.…”
mentioning
confidence: 99%